The effect of valacyclovir on HIV and HSV-2 in HIV-infected persons on antiretroviral therapy with previously unrecognised HSV-2. (July 2015) - Van Wagoner, Nicholas; Geisler, William M; Bachmann, Laura H; Hook, Edward W
In the absence of antiretroviral therapy, valacyclovir may reduce HIV viral load and increase CD4+ T-lymphocyte count. We sought to evaluate the impact of valacyclovir on HIV and HSV-2 in co-infected patients receiving antiretroviral therapy with previously unrecognised HSV-2 infection. A prospective, randomised-controlled, 24-week trial of valacyclovir 1000 mg was performed. Mean CD4+ T-lymphocyte count at 24 weeks compared to baseline CD4+ T-lymphocyte count was the primary outcome. HIV viral load suppression, HSV-2 outbreaks and asymptomatic HSV-2 shedding were secondary outcomes. Participants were randomised to valacyclovir (N = 66) or placebo (N = 35). Study completion was 64%. There was no change in 24 weeks compared to baseline CD4+ T-lymphocyte count in either group (valacyclovir p = 0.91, placebo p = 0.59) or the proportion with HIV viral load suppression (valacyclovir p = 0.75, placebo p = 1.0). Genital HSV and asymptomatic HSV-2 shedding were rare. Valacyclovir had no effect on CD4+ T-lymphocyte count or HIV viral load in this population. Valacyclovir may reduce clinical outbreaks and asymptomatic HSV-2 shedding, but the rarity of these events, along with its lack of benefit on HIV, does not support its use in this clinical setting.